THE INFLUENCE OF SERVICE QUALITY AND PRODUCT QUALITY ON PURCHASE DECISIONS AND CUSTOMER SATISFACTION (MARKETING MANAGEMENT LITERATURE REVIEW) - Wydyanto, Wydyanto; Ridho Rafqi Ilhamalimy (Dinasti International Journal of Management Science, 2021)
The purpose of writing a Literature Review is to determine the effect of service quality and product quality variables on purchasing decision variables and customer satisfaction. With qualitative methods and Library Research. The results showed that service quality had an effect on purchasing decisions, service quality had an effect on customer satisfaction, product quality had an effect on purchasing decisions, product quality had an effect on customer satisfaction and purchasing decisions had an effect on customer satisfaction.